UPAYA MENINGKATKAN POTENSI PAJAK KENDARAAN BERMOTOR MELALUI PENELUSURAN KENDARAAN BERMOTOR TIDAK MELAKUKAN DAFTAR ULANG (KTMDU) DI KELURAHAN HARAPAN JAYA BEKASI UTARA KOTA BEKASI - S. Pentanurbowo (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The motor vehicle is all wheeled vehicles and its wheels are used in all types of landroads, and is driven by engineering equipment in the form of motors or otherequipment that serves to transform a certain energy resource into the mobility of thevehicle in question, with the KTMDU can be aware of motor vehicle taxpayers in orderto perform the inherent obligations, thereby increasing the regional original revenue.West Java provincial Government should coordinate with some elements such as leasing and RT/RW, Coral Taruna per region in order to achieve the right goal.Nowadays motor vehicles are not a luxury goods such as antiquity but nowadaysmotor vehicles have become a necessity and every family seems to already have amotor vehicle it is undeniable that by having a motor vehicle especially motorcyclewill be very supportive of daily activities not regardless of any profession. Having amotor vehicle is the right of everyone but behind the right there are obligations thatmust be fulfilled by the owner of the motor vehicle. Among the obligations on theowner of a motor vehicle is the obligation to make a motor vehicle tax payment once ayear. But what happens is often the obligation is forgotten with a variety of reasons sothat the motor vehicle tax is not paid every year.